Regional anesthesia educational material utilization varies by World Bank income category: A mobile health application data study. - Vanessa Moll; Edward R Mariano; Jamie M Kitzman; Vikas N O'Reilly-Shah; Craig S Jabaley (PLoS ONE)
Introduction Regional anesthesia offers an alternative to general anesthesia and may be advantageous in low resource environments. There is a paucity of data regarding the practice of regional anesthesia in low- and middle-income countries. Using access data from a free Android app with curated regional anesthesia learning modules, we aimed to estimate global interest in regional anesthesia and potential applications to clinical practice stratified by World Bank income level. Methods We retrospectively analyzed data collected from the free Android app "Anesthesiologist" from December 2015 to April 2020. The app performs basic anesthetic calculations and provides links to videos on performing 12 different nerve blocks. Users of the app were classified on the basis of whether or not they had accessed the links. Nerve blocks were also classified according to major use (surgical block, postoperative pain adjunct, rescue block). Results Practitioners in low- and middle-income countries accessed the app more frequently than in high-income countries as measured by clicks. Users from low- and middle-income countries focused mainly on surgical blocks: ankle, axillary, infraclavicular, interscalene, and supraclavicular blocks. In high-income countries, more users viewed postoperative pain blocks: adductor canal, popliteal, femoral, and transverse abdominis plane blocks. Utilization of the app was constant over time with a general decline with the start of the COVID-19 pandemic. Conclusion The use of an in app survey and analytics can help identify gaps and opportunities for regional anesthesia techniques and practices. This is especially impactful in limited-resource areas, such as lower-income environments and can lead to targeted educational initiatives.